Specifying a Causal Role for Angular Gyrus in Autobiographical Memory - Bonnici, Heidi M. (J Neurosci, 2018)
Considerable recent evidence indicates that angular gyrus dysfunction in humans does not result in amnesia, but does impair a number of aspects of episodic memory. Patients with parietal lobe lesions have been reported to exhibit a deficit when freely recalling autobiographical events from their pasts, but can remember details of the events when recall is cued by specific questions. In apparent contradiction, inhibitory brain stimulation targeting angular gyrus in healthy volunteers has been found to have no effect on free recall or cued recall of word pairs. The present study sought to resolve this inconsistency by testing free and cued recall of both autobiographical memories and word-pair memories in the same healthy male and female human participants following continuous theta burst stimulation (cTBS) of angular gyrus and a vertex control location. Angular gyrus cTBS resulted in a selective reduction in the free recall, but not cued recall, of autobiographical memories, whereas free and cued recall of word-pair memories were unaffected. Additionally, participants reported fewer autobiographical episodes as being experienced from a first-person perspective following angular gyrus cTBS. The findings add to a growing body of evidence that a function of angular gyrus within the network of brain regions responsible for episodic recollection is to integrate memory features within an egocentric framework into the kind of first-person perspective representation that enables the subjective experience of remembering events from our personal pasts. SIGNIFICANCE STATEMENT In seeking to understand the role played by the angular gyrus region of parietal cortex in human memory, interpreting the often conflicting findings from neuroimaging and neuropsychology studies has been hampered by differences in anatomical specificity and localization between methods. In the present study, we address these limitations using continuous theta burst stimulation in healthy volunteers to disrupt function of angular gyrus and a vertex control region. With this method, we adjudicate between two competing theories of parietal lobe function, finding evidence that is inconsistent with an attentional role for angular gyrus in memory, supporting instead an account in terms of integrating memory features within an egocentric framework into a first-person perspective representation that enables the subjective experience of remembering.